MAQĀȘID AL-ZUWĀJ AL-SYAR’IYYAH: DIRĀSAH LI AHAMMI MAQĀȘID AL-AȘLIYYAH WA AL-TABA’IYYAH - Ismail Firano (Jurnal Al-Dustur)
The essence of Islamic law lies in promoting and fulfilling the well-being of people while preventing and minimizing harm in their religious and worldly affairs.  Therefore, understanding the objectives of Sharia in the institution of the family is crucial and urgent, especially given the immense challenges faced by Muslim societies today. The primary path to family formation is marriage, which, according to the Quran, is not merely a means for preserving the human race but also a way to achieve psychological reassurance, inner peace, and emotional tranquility.  Islam places great emphasis on the family, providing care and guidance, and outlining the paths that enable it to fulfill its roles in building a strong society characterized by righteousness, justice, love, compassion, harmony, and happiness. To delve deeper into this topic, this study employed a qualitative research methodology, relying on primary sources from the Quran and Sunnah, and secondary sources from books of Tafsir (Quranic exegesis), Fiqh (Islamic jurisprudence), and Usul al-Fiqh (principles of Islamic jurisprudence). When God Almighty connects marriage to the sexual instinct, it is not merely for the fulfillment of desire, but rather to achieve higher purposes, such as establishing the family as the foundation of society and raising children according to the wise principles of Sharia.  Therefore, God has established pillars and conditions for marriage, along with objectives and goals.  When these are observed, marriage fulfills its positive impacts on various aspects of society.  However, neglecting these objectives disrupts the intended purpose of marriage, leading to dysfunction, marital and social problems, and a deviation from the purity, love, and serenity that are desired for life.  These problems can only be addressed by preserving, caring for, and upholding the true objectives of marriage.